The Redefinition of Nullity for Legal Purposes and the Possibility of Annulment Due to the Failure to Fulfill the Validity Requirements of an Agreement (Case Study of Decision No. 31/Pdt/2-2-/PT MDN) - Sabillah, Tasya; Jatmiko, Mamiek (PT. Hafasy Dwi Nawasena, 2024)
The research written by Tasya Sabillah explains the redefinition of nullity for legal purposes and the possibility of annulment due to the failure to meet the validity requirements of an agreement. It discusses the validity of an agreement in relation to the annulment of an agreement in Decision No. 31/Pdt/2-2-/PT MDN, as well as the legal norms that define the annulment of an agreement in this decision. The research, conducted through a literature study and categorized as normative research, results in the Judge's Considerations in the Annulment of the Agreement in Decision No. 31.7/Pdt/2020/PT.Mdn. The main point is that PT. Tarurung had incorrectly applied the law by examining and ruling on the plaintiff's lawsuit, whereas the core dispute in the case was about breach of contract (wanprestasi) between the defendant and the plaintiff based on the cooperation agreement (SPK), which is essentially a contractual case. The legal consequence of the annulment of the agreement in Decision No. 31.7/Pdt/2020/PT.Mdn, as concluded by the judge in the case, is that the decision cannot be executed, making the ruling effectively non-existent.